Long-Term Efficacy and Safety of Repeated Rituximab to Maintain Remission in Idiopathic Childhood Nephrotic Syndrome: An International Study. Issue 6 (June 2022) - Chan, Eugene Yu-hin; Yu, Ellen L.M.; Angeletti, Andrea; Arslan, Zainab; Basu, Biswanath; Boyer, Olivia; Chan, Chang-Yien; Colucci, Manuela; Dorval, Guillaume; Dossier, Claire; Drovandi, Stefania; Ghiggeri, Gian Marco; et al.
Significance Statement: Children with frequently relapsing, steroid-dependent nephrotic syndrome (FRSDNS) often require multiple courses of rituximab. However, long-term effects from repeated treatments remain unknown. In this international, multicenter study of 346 children receiving 1149 courses of rituximab, the risk of relapse decreased and relapse-free survival significantly improved with repeated treatments. Important side effects, including hypogammaglobulinemia, neutropenia, and infections, were mostly mild, but significant adverse events could occur. The incidence of side effects did not increase with more treatment courses nor a higher cumulative dose of rituximab. These findings suggest that repeating rituximab therapy is an effective and reasonably safe approach for most children with FRSDNS. Visual Abstract: Abstract : Background: Long-term outcomes after multiple courses of rituximab among children with frequently relapsing, steroid-dependent nephrotic syndrome (FRSDNS) are unknown. Methods: A retrospective cohort study at 16 pediatric nephrology centers from ten countries in Asia, Europe, and North America included children with FRSDNS who received two or more courses of rituximab. Primary outcomes were relapse-free survival and adverse events. Results: A total of 346 children (age, 9.8 years; IQR, 6.6–13.5 years; 73% boys) received 1149 courses of rituximab. A total of 145, 83, 50, 28, 22, and 18 children received two, three, four, five, six, and seven or more courses, respectively. Median (IQR) follow-up was 5.9 (4.3–7.7) years. Relapse-free survival differed by treatment courses (clustered log-rank test P <0.001). Compared with the first course (10.0 months; 95% CI, 9.0 to 10.7 months), relapse-free period and relapse risk progressively improved after subsequent courses (12.0–16.0 months; HRadj, 0.03–0.13; 95% CI, 0.01 to 0.18; P <0.001). The duration of B-cell depletion remained similar with repeated treatments (6.1 months; 95% CI, 6.0 to 6.3 months). Adverse events were mostly mild; the most common adverse events were hypogammaglobulinemia (50.9%), infection (4.5%), and neutropenia (3.7%). Side effects did not increase with more treatment courses nor a higher cumulative dose. Only 78 of the 353 episodes of hypogammaglobulinemia were clinically significant. Younger age at presentation (2.8 versus 3.3 years; P =0.05), age at first rituximab treatment (8.0 versus 10.0 years; P= 0.01), and history of steroid resistance (28% versus 18%; P =0.01) were associated with significant hypogammaglobulinemia. All 53 infective episodes resolved, except for one patient with hepatitis B infection and another with EBV infection. There were 42 episodes of neutropenia, associated with history of steroid resistance (30% versus 20%; P =0.04). Upon last follow-up, 332 children (96%) had normal kidney function. Conclusions: Children receiving repeated courses of rituximab for FRSDNS experience an improving clinical response. Side effects appear acceptable, but significant complications can occur. These findings support repeated rituximab use in FRSDNS.